Chemical and Microbiological Contamination of Natural Water Resources in Saedinenie, Bulgaria - Slavov, Aleksandar; Goranov, Bogdan; Denkova, Zapryana (Journal of Sustainability and Environmental Management, 2022)
Human impact on the quality of freshwater source creates a risk of long-term pollution in water bodies intended for drinking and irrigation purposes. In the present study, the chemical and microbiological contamination of natural water from two wells and Potoka River of the town Saedinenie, Bulgaria were studied. All groundwater samples showed very high NO3- and Cd2+ content – 400 mg/l and 0,167 mg/l for Well 1 together with 431 mg/l and 0,188 mg/l for Well 2, respectively. Strong contamination with Escherichia coli, Enterococcus faecalis and sulfite-reducing microorganisms was also observed. In both cases limits for drinking purposes were exceeded. NO3--N in the Potoka River was around 4,47 mg/l, i.e. less than the maximum threshold value. However, the amount of Cd2+ was found to be highest in all of the conducted experiments, reaching 0,300 mg/l at permissible values of 0,010 mg/l. This shows all tested samples require pre-treatment before using for any purpose.